Slavery in Charles Dickens’ Novel Oliver Twist - Van Arlin Abas; Indah Wardaty Saud; Dahlia Husain (Universitas Ahmad Dahlan, 2020)
This research discusses the slavery experienced by the characters in the Oliver Twist novel. Those who have no family and no place to stay eventually become slaves who are forced to work for the benefit of the owner. They are treated as property and often get physical violence. This research aims to analyze the types of slavery that are reflected in Oliver Twist novel. This research using descriptive qualitative methods. Researchers used the Marxist approach and slavery theory to find the types of slavery contained in Oliver Twist novel. From the results of the analysis, it was found that there are 4 types of slavery in Oliver Twist novel, namely forced labor, sex slavery, child slavery and domestic servitude.